Search for the rare decays Bs0→μ+μ- and B0→μ+μ- - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; Meißner, Marco; et al. (Physics letters, 2011)
A search for the decays Bs0→μ+μ− and B0→μ+μ− is performed with about 37 pb−1 of pp collisions at s=7 TeV collected by the LHCb experiment at the Large Hadron Collider at CERN. The observed numbers of events are consistent with the background expectations. The resulting upper limits on the branching ratios are B(Bs0→μ+μ−)<5.6×10−8 and B(B0→μ+μ−)<1.5×10−8 at 95% confidence level.
*LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, K. Holubyev, G. Krocker, C. Linn, J. Marks, M. Meissner, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 530 weitere Personen]
Im Titel sind die Zahl 0 sowie die Zeichen + und - hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Gesehen am 16.02.2022